A new expression for crack opening stress determined based on maximum crack opening displacement under tension–compression cyclic loading. Issue 1 (10th July 2017) - Chen, J. J.; You, M.; Huang, Y.
Abstract: The maximum crack opening displacement is introduced to investigate the effect of compressive loads on crack opening stress in tension–compression loading cycles. Based on elastic–plastic finite element analysis of centre cracked finite plate and accounting for the effects of crack geometry size, Young's modulus, yield stress and strain hardening, the explicit expression of crack opening stress versus maximum crack opening displacement is presented. This model considers the effect of compressive loads on crack opening stress and avoids adopting fracture parameters around crack tip. Besides, it could be applied in a wide range of materials and load conditions. Further studies show that experimental results of d a /d N − Δ K curves with negative stress ratios could be condensed to a single curve using this crack opening stress model.